2022
DOI: 10.3390/biomedicines10081826
|View full text |Cite
|
Sign up to set email alerts
|

Combined Hepatocellular-Cholangiocarcinoma: An Update on Pathology and Diagnostic Approach

Abstract: Combined hepatocellular-cholangiocarcinoma (cHCC-CCA) is a rare primary liver carcinoma displaying both hepatocytic and cholangiocytic differentiation within the same tumor. Relative to classic hepatocellular carcinoma (HCC), cHCC-CCA has more aggressive behavior and a poorer prognosis. Though recent advances have improved our understanding of the biology underlying cHCC-CCAs, they remain diagnostically challenging for pathologists because of their morphologic and phenotypic diversity. Accurate diagnosis of cH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 73 publications
(86 reference statements)
0
5
0
1
Order By: Relevance
“…[7][8][9][10][11] However, compelling evidence suggests that proliferative HCCs behave differently from nonproliferative HCCs, with distinct prognoses and prognostic factors. 1,2,[12][13][14][15][16] As mentioned by Kang et al, proliferative HCC is an independent factor for poor over-all survival, higher rate of intrahepatic distant recurrence, and extrahepatic metastasis after curative surgery. In addition, rim arterial phase hyperenhancement at gadoxetate-enhanced MRI was independent predictors for proliferative HCC and poor prognosis.…”
Section: Introductionmentioning
confidence: 94%
“…[7][8][9][10][11] However, compelling evidence suggests that proliferative HCCs behave differently from nonproliferative HCCs, with distinct prognoses and prognostic factors. 1,2,[12][13][14][15][16] As mentioned by Kang et al, proliferative HCC is an independent factor for poor over-all survival, higher rate of intrahepatic distant recurrence, and extrahepatic metastasis after curative surgery. In addition, rim arterial phase hyperenhancement at gadoxetate-enhanced MRI was independent predictors for proliferative HCC and poor prognosis.…”
Section: Introductionmentioning
confidence: 94%
“… 11 Risk factors associated with the development of cHCC-CCA, such as hepatitis B, hepatitis C, and cirrhosis, are similar to those of HCC in Asian populations. 12 However, studies conducted in Europe and the USA have reported that most cases of cHCC-CCA occur without accompanying chronic liver diseases and arise de novo. 13 These findings suggest that geographical factors may influence the clinical characteristics of patients with cHCC-CCA.…”
Section: Clinical Characteristicsmentioning
confidence: 99%
“… 30 It is worth noting that prominent pseudoglands commonly found in conventional HCC tend to be mistakenly identified as true glandular structures and the reactive ductular reaction at the edge of HCC tends to be considered as an ICC component, leading to the misdiagnosis of cHCC-CCA. 12 Some variants of ICC and ICC arising adjacent to hepatocellular nodular lesions (nodular regenerative hyperplasia) may have histopathological features that resemble cHCC-CCA. However, regardless of the differentiation and immunophenotype, ICC lacking a distinct HCC component should not be diagnosed as cHCC-CCA.…”
Section: Pathological Diagnosismentioning
confidence: 99%
See 1 more Smart Citation
“…Ayrıca kombine hepatoselülerkolanjiyokarsinom tümörleri de nadir olarak gözlenen primer karaciğer malignitelerinden biridir ve histolojik olarak karışık bir kanser türü olduğundan dolayı noninvaziv ve doğru teşhisin konulması hemen hemen imkansızdır [5,6]. Bunun yanı sıra klinikte LIHC ve iCHOL'ün ameliyat öncesi süreçte noninvaziv ayırıcı tanısının esas olarak görüntülemeye dayandığı bilinmektedir.…”
Section: Introductionunclassified